Manajemen Kurikulum Pendidikan Islam Berbasis Multikultural - Rohmat Rohmat (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: This article attempts to create a reflection of the Islamic educational curriculum, and some alternative Islamic education curriculum based of multicultulral. As for some of the underlying assumptions, that the practice of teaching Islamic education was oriented toward mastery of teaching material has not been oriented toward understanding and awareness creation on respect for diversity of race, ethics, culture. Islamic Education as one of the important aspects as the formation of character, should have the concept that learing is more directed at the character formation of children and respect for cultural diversity. Thus, to Look forthe development of Islamic education curriculum model (Madrasah Aliyah) based of multicultural. Management of multicultural based Islamic education can be through several phases: content integration, the knowledge construction process, an equity paedagogy, and prejudice reduction. The focus of management of multicultural based curriculum Islamic education should be directed to find the msdel of Islamic education (Madrasah Aliyah) that can explore humanist values and universal. Islamic education learning design (Madrasah Aliyah) based mutticultural directed the efforts to form the character of the appreciation and respect for diversity of thought, concept, and culture. Development of leaming modets of Islamic education in Madrasah Aliyah multicultural-based refers to a balanced composition of matter Koran, Hadith , fiqh, aqidah, and akhlak. Keywords: Management of curriculum, Education, Multicultural.